The Evaluasi Penggunaan Antibiotik Pada Pasien Dispepsia Komplikasi Demam Tifoid di Rumkit Putri Hijau Medan 2018 - Desy Natalia Siahaan; Burham Burham; Reny Ayu Zendrato (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Antibiotics are substances that are produced by microorganisms that live from fungi that can fight or can fight other types of microbes. The use of higher antibiotics can be used in the use of antibiotics that are not rational. This research aims to improve the quality and quality of antibiotic use in inpatients at Patients with dyspepsia and complications of typhoid fever at TK Hijau Putri II Hospital, Kesdam I / BB Medan in 2018.The study was conducted descriptive descriptive with cross sectional research design with retrospective data collection conducted during the 2018 period. Quantitative evaluation research used the DDD (Defined Daily Dose) method and qualitative evaluation using the Gyssens category.The results showed that of the 120 patients using antibiotics, the quality assessment of the Gyssens category obtained results of 90% category 0 (rational), 10% category IIIA (duration too long). Evaluation of the amount by the DDD method (Daily Dose Determined) obtained the use of antibiotics with a DDD value / 1000 patient-day the highest was the fluoroquinolone group (ciprofloxacin and levofloxacin) with 56.4%, while for ciprofloxacin used 1,213 DDD / 1000 Patient-day and for levofloxacin have 1,000 DDD / 1000 Patient-days. Antibiotics for the third generation cephalosporins (cefotasim and ceftriaxone) with 43.14%, while for cefotasim have 713 DDD / 1000 Patient-days and for ceftriaxone have 1,000 DDD / 1000 Patient-days.